INCORPORATION OF A TWO-FLUX MODEL FOR RADIATIVE HEAT TRANSFER IN A COMPREHENSIVE FLUIDIZED BED SIMULATOR PART I: PRELIMINARY THEORETICAL INVESTIGATIONS - Rabi, J. A.; de Souza Santos, M. L. (Revista de Engenharia Térmica, 2003)
Over the last two decades, a comprehensive mathematical model and its corresponding computational program, aimed to simulate steady-state operations of bubbling fluidized bed equipments, has been continuously improved and tested. Despite its success, the simulator has employed a simple approach for radiative heat transfers. In cases of high temperatures, thermal radiation becomes an important energy transfer mode and the original model could lead to deviations above acceptable levels. The purpose of the present work was to improve the model for thermal radiation heat transfer between all solid particles in the bed section by applying a two-flux method to a non-homogeneous polydispersed particulate media in radiative equilibrium. Gases in the emulsion and in the bubbles were assumed transparent to thermal radiation. This first part of the paper presents and discusses the basic structure of the former mathematical model and of the new one.